Prevalence and Antibiotic Susceptibility Pattern of Foodborne Bacterial Pathogens Isolated From Spoiled Vegetables at Wolaita Sodo Town, South Ethiopia - Krishna Moorthy Sivalingam; Destahun Samuel Sama; Subramaniyan Vaithilingam (Journal of Food Quality)
Foodborne bacterial pathogens and related diseases are a major public health concern worldwide. Vegetables are a major healthy diet in our lives and an extraordinary dietary source of nutrients such as calcium, magnesium, vitamins, minerals, iron, and fiber. Because of their high moisture and low acidity, they provide a medium for foodborne pathogens. Foodborne bacterial pathogens or their toxins can affect consumer’s health and may even lead to death when foods are contaminated with them. However, there was no previous research in the study area related to spoiled vegetables and foodborne pathogens. Therefore, this study was conducted to determine the prevalence of foodborne bacterial pathogens by isolation and identification, and antibiotic susceptibility profile of foodborne pathogenic bacteria isolated from spoiled vegetables. A total of 96 samples of three different vegetables were randomly collected from vendors in the public market of Wolaita Sodo Town. All the samples were processed by standard microbiological techniques for enumeration of total viable count, selective media isolation and biochemical identification, and antibiotic susceptibility patterns using standard antibiotics. The total viable count was very high in cabbage (10.8 ± 0.29 × 105 cfu/gm) followed by tomato (8.1 ± 0.27 × 105 cfu/gm) and carrot (6.6 ± 0.26 × 105 cfu/gm). The most frequently isolated bacterial pathogen was Staphylococcus aureus with a 28.12% prevalence rate followed by Escherichia coli at 26%, Salmonella spp. at 14.58%, and Shigella spp. at 6.25%. The isolated E. coli, Salmonella spp., Shigella spp., and S. aureus strains were highly resistant to respective antibiotics cloxacillin, vancomycin, ceftriaxone, and ampicillin. All the bacterial isolates showed resistance to ampicillin, amoxicillin, and cloxacillin and were highly susceptible to ciprofloxacin, gentamicin, tetracycline, and chloramphenicol. The presence of foodborne bacterial pathogens with resistance to several antibiotics is a serious public health concern in the study area. Therefore, regular monitoring of the quality of vegetables and enteric bacterial infections among vendors and farmers should also be informed about the sources of microbial contamination.